Ethnolinguistic Characteristics of Usernames in the Virtual Environment of Kalmykia - Daldinova, Elza O.-G.; Kekeeva, Tatyana M.; Kichikova, Nadezhda A.; Mikitenko, Nina Yu. (The New Research of Tuva, 2025)
This article analyzes the ethnic component of anthroponymic units (usernames) identified in the virtual communication of residents of Kalmykia. The data for analysis consisted of usernames of members of online communities discussing a variety of issues pertaining to the public life of the republic on the “VKontakte” (VK) social network platform.The role of online nicknames in virtual communication is determined. Trends are identified in which Internet users choose usernames based on the traditions of traditional Kalmyk culture. The implementation of ethnic elements is reflected in the semantics of proper and common nouns within usernames. Semantic groups are identified in which the ethnic component of usernames is expressed. These groups include nicknames that reference personal names, physical appearance, nationality, and regional affiliation. Usernames containing plant names (phytonyms) and place names (toponyms) are also analyzed.A notable feature of usernames among Internet users from the Kalmyk segment of VKontakte is their two-part structure, predominantly consisting of a given name and surname, less frequently including a patronymic. Instances of name borrowing from various languages are noted. An active use of ethnic Kalmyk vocabulary is observed. The semantics of the analyzed usernames reflect traditional rituals.Usernames of Internet users from Kalmykia serve as important elements in constructing identity and cultural uniqueness, functioning as distinctive markers that reflect both individual and collective features of users.
Keywords: Kalmyk language; ethnolinguistics; ethnolinguocultural studies; nickname; virtual communication; social network; virtual onomasticon; Kalmyks; Republic of Kalmykia